TUBERCULOSIS PREVENTIVE THERAPY AS A STRATEGY TO PREVENT AND CONTROL TUBERCULOSIS INCIDENCE 2010-2024: A BIBLIOMETRIC ANALYSIS: Terapi Pencegahan Tuberkulosis sebagai Strategi Pencegahan dan Pengendalian Kejadian Tuberkulosis 2010-2024: Analisis Bibliometrik - Sari, Yunita; Choirul Hidajah, Atik; Sahiral Layaly, Nur; Susilastuti, Fransisca (Jurnal Berkala Epidemiologi, 2025)
Background: Tuberculosis Preventive Therapy (TPT) is important in TBC control and elimination strategies at the individual and community levels. However, few studies have systematically mapped developing scientific themes and trends related to TPT, primarily through bibliometric analyses. Therefore, a comprehensive bibliometric study is needed to identify key research foci and gaps in the current TPT knowledge pool. Purpose: This study aimed to identify global research trends in TPT as a preventive strategy to reduce TBC incidence. Methods: This study used a systematic literature review approach and bibliometric analysis using Scopus and PubMed databases through the Publish or Perish (PoP) platform, publications from 2010 to 2024. The initial search yielded 266 articles, which were screened using Mendeley for abstracts and keywords, resulting in 109 relevant publications. Bibliometric analyses were then conducted using VOSviewer version 1.6.20. Results: IPT (Isoniazid Preventive Therapy) has a close relationship with Preventive therapy, tuberculosis, child, contact, and HIV. Other results also show that the number of publications discussing TPT from 2020 to 2024 has decreased from 23 to 2, and the latest research topics related to TPT were only found in 2019. Conclusion: Publications related to TPT from 2020-2024 continue to decline; therefore, it is necessary to revitalize research related to TPT, especially by exploring issues that have not been widely discussed, such as the implementation of TPT in high-risk groups other than children and PLHIV, such as people with chronic diseases, the elderly, and populations with limited access to health services.